Adaptation and Validation of Nomophobia Instrument (NMP-Q) in the Indonesian Version - Idi Warsah; Aprezo Pardodi Maba; Endang Prastuti; Ruly Morganna; Berliani Aslam Alkiromah Warsah; Eko Carles (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
Type of nomophobia emerges from the prevalence of excessive use of smartphones. The Nomophobia Instrument (NMP-Q) has been adapted across several countries and languages. Still, there have been few studies that have adapted and tested the psychometric properties of the NMP-Q. Thus, this study aimed to linguistically and culturally adapt and validate the Indonesian version of NMP-Q (NMPQ-10). The adaptation process involved experts in language and psychology. The NMPQ-10 in the Indonesian version was validated by involving 276 college students from public universities in Indonesia aged 17 to 24 years old. The results revealed that empirical data supported the overall measurement model of NMPQ-10. The internal structure of NMPQ-10 in the Indonesian version was similar to that of the original version. The Indonesian version of NMPQ-10 also had high psychometric properties, as indicated by the composite reliability (CR) of 0.932 and a Cronbach Alpha of 0.97. Both were classified as high and evident in internal structure (satisfactory construct validity and convergent validity). This study has important implications for counseling practice, as counselors can use the NMPQ-10 to identify individuals experiencing high levels of nomophobia and guide interventions and treatment plans accordingly. In conclusion, the Indonesian version of NMPQ-10 can be utilized to assess nomophobia among college students. Further studies are needed to include a larger sample to improve the validation of NMPQ-10.